Elucidating the roles of miR-372 in cell proliferation and apoptosis of nasopharyngeal carcinoma TW01 cells - Tan, J.K.; Tan, E.L.; Gan, S.Y. (Experimental Oncology, 2014)
Aim: Deregulation of microRNA has been associated with cancer progression and the modification of cancer phenotypes could be achieved by targeting microRNA expression. This study aimed to determine the effects of miR-372 on cell progression and gene expression in nasopharyngeal carcinoma cell line, TW01. Materials and Methods: NPC TW01 cells were transfected with the miR-372 precursor molecules. Gene expression studies were conducted using RT-PCR assays for nine cancer related genes. The effects of miR-372 on cell proliferation, cell cycle arrest and apoptosis were also investigated. Results: Expression of miR-372 caused cell cycle arrest at the S phase that was accompanied by an overall decrease of cells entering the G2/M phase. miR-372 did not have any significant effect on apoptosis. Of the nine genes studied, four were up-regulated, namely CDKN1A, INCA1, LATS2 and BIRC5. The other five genes — CDK2, CCNA1, TP53, BAX and BCL2 were down-regulated by miR-372. Conclusion: This preliminary study indicated the tumor suppressing roles of miR-372 in cell cycle progression of TW01 cells, possibly via the down-regulation of CDK2 and CCNA1 as well as the up-regulation of CDKN1A and INCA1.Key Words: apoptosis, microRNA, nasopharyngeal carcinoma, miR-372, CDK2, CCNA1.